2011
DOI: 10.1103/physreva.84.043422
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal Sisyphus effect for atoms in a toroidal all-optical trap

Abstract: It is shown that an optical arrangement in which two identical counterpropagating Laguerre-Gaussian doughnut beams LG(l,0) and LG(−l,0) with orthogonal linear polarizationsê x andê y can lead to azimuthal polarization gradients and an as yet undiscovered azimuthal Sisyphus effect. It is demonstrated that this effect can be utilized in the creation and control of a persistent current of superfluid atoms circulating in a toroidal trap. Such a physical system has recently been highlighted as the basis for an atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…More subtle quantum e↵ects due to the interaction of optical vortices with atoms and molecules involve internal atomic transitions at near resonance with the beam frequency. Here too, optical forces and torques are at play (Allen et al, 1996a;Andersen et al, 2006;Babiker et al, 1994;Lembessis et al, 2011;Surzhykov et al, 2015), leading to the trapping and manipulation of individual atoms in certain regions of the beam profile, with promising applications in the new field of atomtronics (Andersen et al, 2006;Lembessis and Babiker, 2013;Pepino et al, 2010;Seaman et al, 2007), as well as the proposed generation of atom vortex beams (Hayrapetyan et al, 2013;Lembessis et al, 2014). A related recent advance in matter vortex beams is the realisation of neutron vortex beams in the laboratory (Clark et al, 2015).…”
mentioning
confidence: 99%
“…More subtle quantum e↵ects due to the interaction of optical vortices with atoms and molecules involve internal atomic transitions at near resonance with the beam frequency. Here too, optical forces and torques are at play (Allen et al, 1996a;Andersen et al, 2006;Babiker et al, 1994;Lembessis et al, 2011;Surzhykov et al, 2015), leading to the trapping and manipulation of individual atoms in certain regions of the beam profile, with promising applications in the new field of atomtronics (Andersen et al, 2006;Lembessis and Babiker, 2013;Pepino et al, 2010;Seaman et al, 2007), as well as the proposed generation of atom vortex beams (Hayrapetyan et al, 2013;Lembessis et al, 2014). A related recent advance in matter vortex beams is the realisation of neutron vortex beams in the laboratory (Clark et al, 2015).…”
mentioning
confidence: 99%
“…The coherent superpositions of vortices of different circulation quantum numbers, especially vortex-antivortex cases [28,29], yield interesting interference effects with potential applications [30,31], such as manipulating the chirality of twisted metal nano-structures [32]. Creation of matter-wave vortex states from a non-rotating BEC by two-photon Raman transition method under paraxial LG and Gaussian (G) pulse is well discussed in literature [27,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In these studies, matter-wave vortex is shown to acquire vorticity equal to the winding number of the LG beam.…”
Section: Creation Of Superposition Of Bec Vortex Statesmentioning
confidence: 99%
“…The most conducive way to prevent the loss of the particles from the trap is to incorporate toroidal optical traps [21], [22]. In such traps there will be no reflections because of the absence of any boundary and the particles following H + branch will always remain in this branch and we can realize the Landau physics for these neutral atoms.…”
Section: Realization Of the Landau Physics Of Neutral Atoms In Omentioning
confidence: 99%